1989
DOI: 10.1128/aac.33.7.1118
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability in healthy volunteers of ciprofloxacin administered through a nasogastric tube with and without enteral feeding

Abstract: The bioavailability of ciprofloxacin after its administration through a nasogastric (NG) feeding tube was studied in six healthy volunteers. Each subject received, on separate occasions, an intact 750-mg ciprofloxacin tablet, a crushed tablet as a suspension through an NG tube, and a crushed tablet as a suspension through an NG tube while receiving enteral feeding. No statistically significant differences were observed in the area under the curve, maximum concentration in serum, and time to peak concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…The absorption characteristics (Cm., Tm., AUCG,) of both fluoroquinolones when administered with water were similar to those reported by other investigators (34,48). Ensure significantly decreased the Cm,, and AUCOO,, while it lengthened the Tm.…”
Section: Resultssupporting
confidence: 78%
“…The absorption characteristics (Cm., Tm., AUCG,) of both fluoroquinolones when administered with water were similar to those reported by other investigators (34,48). Ensure significantly decreased the Cm,, and AUCOO,, while it lengthened the Tm.…”
Section: Resultssupporting
confidence: 78%
“…10 Thus, the fact that a tablet may be crushed and administered orally mixed in food or provided as a water suspension via a nasogastric (NG) tube provides an important alternative method of drug administration for these patients. 11,12 However, crushing a tablet and administering it as a suspension might alter the pharmacokinetics of the compound. Additionally, administering a suspension via an NG tube may alter the amount of drug delivered to the GI tract due to drug adsorption onto the luminal surface of the tube.…”
mentioning
confidence: 99%
“…The absorption of temafloxacin and ciprofloxacin is not significantly altered in the presence of Osmolite ® enteral feedings [105,106]. However, other studies have found significant interaction potential between the quinolones and enteral feedings.…”
Section: Absorption Interactionsmentioning
confidence: 96%